Chair Talks - Tim Hatfield; Susan Hatfield; Christian Hansen (Academic Chairpersons Conference Proceedings, 2016)
Dr. Susan Hatfield, "WHAT NO ONE TELLS YOU BEFORE YOU BECOME CHAIR" Some brief insights related to hindsight to promote foresight. Dr. Tim Hatfield, "BEING THERE FOR THE DEPARTMENT WITHOUT LOSING YOURSELF" Few chairs ever assume that position with a deep understanding of the multiple stresses inherent in the role. This talk will address a number of ways to successfully manage the inevitable stresses that chairs face every day. Dr. Christian Hansen, "RIGHT ON TIME: STAYING ON TOP OF THINGS WHEN EVERYBODY WANTS SOMETHING FROM YOU" Department Chairs often find themselves buried in demands from faculty, administration, students and outside entities. This talk will provide tips on how to manage this complex and constantly evolving workload.
Keywords: Chair Talks